Russia's interventions: Counterrevolutionary power - Vladimir Gligorov (The Vienna Institute for International Economic Studies (wiiw), 2016)
The key point is about Russia, old and new, being a counterrevolutionary power: Russia's post- Napoleonic War and moreover post-1848 policy was counterrevolutionary abroad and conservative, even when reformist, at home, as is Russia's current post-Soviet, post-Cold War policy. However, while the current foreign policy end is Russian, the instruments of intervention, e.g. in Syria, are Soviet. The main difference as compared to both, Tsarist Russian and Soviet, is Russia's lack of a universalistic ideological justification now, notwithstanding all the attempts to revive the ideology of the Russian cultural and civilizational exceptionalism to supress liberal changes at home, and for that reason also abroad.
Keywords: N40; N43; N44; O14; F15; 330; Russia; foreign policy; industrialisation; EU